2020
DOI: 10.1002/smll.202001805
|View full text |Cite
|
Sign up to set email alerts
|

Smart Porous Core–Shell Cuprous Oxide Nanocatalyst with High Biocompatibility for Acid‐Triggered Chemo/Chemodynamic Synergistic Therapy

Abstract: The rational integration of chemotherapy and hydroxyl radical (·OH)‐mediated chemodynamic therapy (CDT) holds great potential for cancer treatment. Herein, a smart biocompatible nanocatalyst based on porous core–shell cuprous oxide nanocrystals (Cu2O‐PEG (polyethylene glycol) NCs) is reported for acid‐triggered chemo/chemodynamic synergistic therapy. The in situ formed high density of hydrophilic PEG outside greatly improves the stability and compatibility of NCs. The porosity of Cu2O‐PEG NCs shows the admirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 51 publications
2
94
0
1
Order By: Relevance
“…reported porous core‐shell cuprous oxide nanocrystals (Cu 2 O‐PEG) NCs with smart biocompatible catalytic performance for acid‐triggered chemo/chemodynamic synergistic therapy (Figure 5c). [ 69 ] The results showed that satisfactory porosity and stability promote the chemotherapeutic drug DOX to be loaded into Cu 2 O‐PEG NCs through physical absorption and the strong π–π stacking interaction. What's more, the release of Fenton‐like catalyst Cu + and chemotherapeutic drug DOX would be stimulated by acidy but suppressed in neutral condition (Figure 5d).…”
Section: Nanomaterials‐based Nanoplatforms For Combination Therapy Of Cdt With Other Therapeutic Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…reported porous core‐shell cuprous oxide nanocrystals (Cu 2 O‐PEG) NCs with smart biocompatible catalytic performance for acid‐triggered chemo/chemodynamic synergistic therapy (Figure 5c). [ 69 ] The results showed that satisfactory porosity and stability promote the chemotherapeutic drug DOX to be loaded into Cu 2 O‐PEG NCs through physical absorption and the strong π–π stacking interaction. What's more, the release of Fenton‐like catalyst Cu + and chemotherapeutic drug DOX would be stimulated by acidy but suppressed in neutral condition (Figure 5d).…”
Section: Nanomaterials‐based Nanoplatforms For Combination Therapy Of Cdt With Other Therapeutic Modalitiesmentioning
confidence: 99%
“…Reproduced with permission. [ 69 ] Copyright 2020, Wiley‐VCH. e) Schematic illustration of the design of TPGS‐functionalized Cu 3 BiS 3 NCs with strong absorption in the second NIR window for radiation therapy enhancement.…”
Section: Nanomaterials‐based Nanoplatforms For Combination Therapy Of Cdt With Other Therapeutic Modalitiesmentioning
confidence: 99%
“…Another major feature was the overexpression of H 2 O 2 in tumor cells, and released Mn 2+ could convert endogenous H 2 O 2 into highly toxic • OH with the assistance of HCO 3 − /CO 2 physiological buffer. [34,35] As shown in Figure 3B, methylene blue (MB) was degraded by • OH as an indicator, which could be used to detect the production of • OH. As the concentration of GSH increased from 0 to 5 mm, the MB was degraded in the presence of GSH-response PEG-Au@HMnMSNs and H 2 O 2 .…”
Section: Gsh Depletion-enhanced • Oh Generationmentioning
confidence: 99%
“…化疗药物的高毒性和某些癌细胞的 耐药性抑制了其单一应用的前景. 癌细胞缺氧环境抑 制了PDT效果, 有研究者为了克服癌细胞周围缺氧的 局限性, 将声动力疗法作为替代疗法 [78] . Wan等 [79] [80] 通过在Au 图 6 章鱼型PEG-Au-PAA/mSiO 2 -LA Janus NPs的制备及在体内外抗癌研究 [71] (网络版彩图) [81] .…”
Section: 自组装法unclassified